Análisis de la inversión extranjera en Colombia en el sector de hidrocarburos y su gestión: caso de estudio Pacific Rubiales 2010-2015 (2019)
This monograph is carried out with purely academic purposes which explains the hydrocarbons outlook during the period that includes the years 2010-2015. The document presents the behavior of the hydrocarbons market in a general way in the world and then becomes more specific happening by the country (Colombia) and by the company PACIFIC RUBIALES, issues of the hydrocarbons industry will be addressed and in the end the factors that triggered the company to close are exposed.